The distribution of marine debris along the Pahang coastline, Malaysia during the Southwest and Northeast Monsoons - Azman, Muhammad Afiq; Ramli, Muhammad Zahir; Che Othman, Siti Fairuz; Shafiee, Saiful 'Arifin (Elsevier, 2021)
This study investigated the accumulation of debris at four sites, namely, Gebeng, Batu Hitam, Cherok Paloh, and Air Leleh, along the Pahang coastline, Peninsular Malaysia from March 2019 to February 2020. Plastic was the dominant debris (86.1%) and followed by cloth/fabric-based debris (6.0%), processed lumber debris (3.3%), rubber (2.7%), glass (1.5%), and metal (0.4%). The land-based debris (82.0%) was the major source of the deposition of marine waste. A statistically significant relationship was found between the seasonal variation and marine debris density in tidal and seasonal current along the Pahang coastline. In general, the Northeast Monsoon season had a higher amount of debris than the Southwest Monsoon season.